2017
DOI: 10.4314/tjpr.v15i12.25
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of voluntarily reported medication errors among adult patients in intensive care (IC) and non- IC settings in Riyadh, Saudi Arabia

Abstract: [OR = 5.24, 95 % CI: (4.12, 6.65); p < 0.001] and with patients' age ≥ 60 vs. < 60 years [OR = 1.48, 95 % CI: (1.19, 1.83

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…12 The highest rate of MEs was 5.5% found in intensive care units (ICUs). 16 Most of MEs were for inpatient prescriptions. 17 For every 100 prescriptions, there were 1.5 medication errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The highest rate of MEs was 5.5% found in intensive care units (ICUs). 16 Most of MEs were for inpatient prescriptions. 17 For every 100 prescriptions, there were 1.5 medication errors.…”
Section: Introductionmentioning
confidence: 99%
“…13 The implementation of a "culture of safety" and "just culture" might help the staff to understand the importance of patient safety and further enhanced reporting of medication errors. 16 The health-care organization should adopt a program that enhances and promotes error reporting, based on transparency, confidentiality, and no-blame culture. 33 Electronic prescribing systems help to reduce medication errors, although they do not prevent all errors.…”
mentioning
confidence: 99%
“…Further, similar to other literature, the location of MAEs often occurred in intensive care units (ICU) and medical units. [16,28,45,46] The results of this study may be partially due to the greater frequency of medications being administered in the medical units compared to that in the ambulatory units. Further, underreporting of errors in surgery may offer another explanation as this underreporting by physicians has been reported elsewhere.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to other studies, the majority of MAEs resulted in no or minimal harm. [7,16,28,49] However, a recent study conducted revealed that over half of the adverse drug events were significant (52.7%), with 37.1% being serious, 9% life-threatening, and 3% fatal. [28] Study results delineated that staff factors contributing to MAEs (e.g., staff not following policies and procedures [14,42] and heavy workloads [27] ) are similar to other results in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation